The Magic of Concepts : History and the Economic in Twentieth-Century China - Karl, Rebecca E. (Book collections on Project MUSE., 2017)
Rebecca E. Karl interrogates the concept and practice of "the economic" as it was understood in China in the 1930s and the 1980s and 90s, showing how the use of Eurocentric philosophies, narratives, and conceptions of the economic that exist outside lived experiences fail to capture modern China's complex history.